Nanometer refractive index sensor based on water droplet cavity structure with rectangular short rod - Wang, Jin; Yan, Shubin; Liu, Feng; Chang, Shuwen; Cao, Yuhao; Cui, Yang; Liu, Jilai; Zhang, Yi; Ren, Yifeng (Frontiers in Physics, 2024)
In this paper, a novel nano sensor structure is proposed, which consists of a metal-insulator-metal waveguide (MIM) with rectangular baffles and a water droplet cavity with rectangular stubs (WDCRS). The WDCRS structure optimizes the sensitivity of a single water droplet cavity and makes the transmission curve clearer and smoother. The transmission characteristics of WDCRS structure were simulated using finite element method(FEM). The transmission characteristics of the exported structure were analyzed in detail. In addition, the influence of structural geometric parameters on sensing performance was also studied, and it was found that the size of the water droplet cavity is a key factor in improving sensitivity. When applied to a refractive index sensor, the structure achieves a sensitivity of up to 2300 nm/RIU with a corresponding figure of merit (FOM) of 60.5. These works provide some ideas for the design of high-performance nanostructures and multiple Fano resonance excitation structures.